2014
DOI: 10.5021/ad.2014.26.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofSfrp2Is Increased in Catagen of Hair Follicles and Inhibits Keratinocyte Proliferation

Abstract: BackgroundHair follicles undergo cycles of repeated growth and regression. The Wnt pathway plays an important role in the regeneration and differentiation of hair follicles. Sfrp2, a Wnt inhibitor, is involved in the developmental and disease processes of various cells and tissues by modulating the Wnt pathway.ObjectiveThe aim of this study was to understand the role of Sfrp2 in hair follicles through investigation of the Sfrp2 expression pattern in the skin and its effect on keratinocytes.MethodsWe investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…In the skin, the role of sFRP2 was previously observed during the epithelial-mesenchymal interaction in the hair follicle (Kim and Yoon, 2014;Rendl et al, 2005). It was shown that sFRP2 is expressed in the dermal papilla and in the matrix of hair follicles (Rutberg et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…In the skin, the role of sFRP2 was previously observed during the epithelial-mesenchymal interaction in the hair follicle (Kim and Yoon, 2014;Rendl et al, 2005). It was shown that sFRP2 is expressed in the dermal papilla and in the matrix of hair follicles (Rutberg et al, 2006).…”
Section: Discussionmentioning
confidence: 85%
“…While DKK1 expression remained unchanged in our study, expression of SFRP2 was significantly increased in > 80% of our patients with AGA ( P < 0·002). SFRP2 , expressed in the epithelial portion of HFs, has been shown to be involved in hair fibre differentiation, and in the catagen phase by inhibiting keratinocyte differentiation …”
Section: Resultsmentioning
confidence: 99%
“…Skin and hair follicle development-related genes play different roles at the various stages of hair follicle development. For example, SFRP2 is principally expressed during the degenerative phase [8]. DDK1 is an inhibitor of the classical Wnt signaling pathway and is mainly expressed during the growth phase [32].…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 promotes the proliferation of dermal papillae and mitosis of true skin fibroblasts [35]. During catagen of hair follicles, SFRP2 affects skin and hair follicle development by inhibition of keratinocyte proliferation and Wnt activity [8] and DKK1 has been shown to promote the regression of hair follicles [37]. The expression levels of all these genes changed significantly after overexpression of SIAH1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation